Methionine as a Semen Additive to Improve Murrah Buffalo (Bubalus bubalis) Semen Cryopreservation - Verma, Abhishek Kumar; Kumar, Rabindra; Srivastava, Sushant; Alam, Kabir; Kumar, Rajesh; Sakhahari, Daund Sushant; Verma , Sanjeev Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The aim of the present investigation was to evaluate the impact of methionine at different concentrations (2.0 mM and 2.5 mM) on the seminal parameters before and after cryopreservation of extended Murrah bull semen. Thirty-six ejaculates, collected with the aid of an artificial vagina twice a week from six Murrah bulls, were included in the study. Each ejaculate was diluted in a Tris-citric-acid-fructose egg-yolk-glycerol (TFYG) extender keeping 80 million sperm per mL and split into three equal aliquots, which were supplemented with methionine 0.0, 2.0 and 2.5 mM; Treatment C, T1 and T2, respectively), filled in 0.25 mL straws, cooled to and equilibrated for 4 h at 4° C, and then frozen in LN2 vapour. Frozen straws were thawed at 37°C for 30 seconds in a water bath for the post-thaw evaluation. Sperm motility, percent live sperm, sperm abnormalities, in-vitro fertility tests (HOST and CMPT), and enzyme leakage (AST, ALT) were evaluated at both post-dilution and post-thaw stages. The results revealed that the addition of methionine, at both 2.0 mM and 2.5 mM concentrations significantly (P<0.05) improved sperm motility, sperm livability, and HOS-positive spermatozoa. Further, the sperm abnormalities and enzyme leakage were significantly (P<0.05) lower in methionine-treated groups than in control group. The results were the best with 2.5 mM methionine supplementation. In conclusion, the study showed that methionine at a concentration of 2.5 mM exhibited superior protection of sperm structures and functions as compared to 2.0 mM methionine and the control group.